Czym jest dziś czytanie literatury? (ankieta) - Majda, Rafał (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2013)
The author talks about his reading fascinations. He talks about the pleasure of reading Sienkiewicz’s novels and Pan Tadeusz, about writings by authors from the former Yugoslavia, and finally – about the travel literature.